Globalization and Executive Compensation - Wolfgang Keller; William W. Olney (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper identifies globalization as a factor behind the rapid increase in executive compensation and inequality over the last few decades. Employing comprehensive data on top executives at major U.S. companies, we show that compensation is higher at more global firms. We find that pay responds not only to firm size and technology but also to exports conditional on other firm characteristics. Export shocks that are not related to the executive's talent and actions also increase executive compensation, indicating that globalization is influencing compensation through pay-for-non-performance. Furthermore, this effect is asymmetric, with executive compensation increasing due to positive export shocks but not decreasing due to negative shocks. Finally, export shocks primarily affect discretionary forms of compensation of more powerful executives at firms with poor corporate governance, as one would expect if globalization has enhanced rent-capture opportunities. Overall, these results indicate that globalization has played a more central role in the rapid growth of executive compensation and U.S. inequality than previously thought, and that both higher returns to top talent and rent-capture are important parts of this story.
Keywords: F16; F14; F66; M12; J31; 330; inequality; executive compensation; globalization; exports